Changes in the neuromuscular system of the lateral extraocular muscles after electrical stimulation of the lateral rectus muscle in children with nonaccommodative comitant esotropia (Ukrainian Journal of Ophthalmology, 2026)
Background: Electrical stimulation of the lateral rectus muscles (LRMs) is a physiotherapeutic technique used in the treatment of comitant esotropia. Post-treatment changes in the neuromuscular system of the eye have been not estimated previously due to the lack of an appropriate method for investigating the electrical activity of the extraocular muscles (superficial electromyography (sEMG) technique).Purpose: To employ the recently developed ocular sEMG technique in order to assess changes in the neuromuscular system of the eye in comitant esotropia before and after electrical stimulation of the LRMs.Materials and Methods: Twelve children (24 eyes) with comitant esotropia underwent electrical stimulation of the LRMs using the Amplipuls-5 apparatus. In addition, an electromyography recorder (M-TEST-2) was used to assess the function of the muscles in accordance with our sEMG methodology before and after treatment.Results: After treatment, the amplitude of the sEMG signal from the LRM insignificantly decreased from 11.55 ±2.3 to 10.64 ± 0.7 mV (p > 0.05), whereas the frequency significantly increased from 49.7 ± 3.6 to 63.18 ± 8.2 Hz (p < 0.05). In addition, the amplitude and frequency of the sEMG signal from the medial rectus muscle insignificantly (p > 0.05) decreased, from 11.48 ± 0.5 mV to 10.2 ± 0.9 mV and from 101.96 ± 5.6 Hz to 94.7 ± 19.5 Hz, respectively.Conclusion: The sEMG technique allows for estimating changes in frequency and amplitude of the response of the LRMs before and after electrical stimulation. In children with comitant esotropia, an improvement in the imbalance between the activity indices of lateral and medial rectus muscles was observed after electrical stimulation of the extraocular muscles.
Keywords: electrical stimulation of extraocular muscles; superficial electromyography; comitant esotropia